Yield loss prediction for integrated weed management in direct-seeded rice - Fischer, Albert J.; Lozano, J.C.; Ramírez Suárez, A.; Sanint, Luis Roberto (International Center for Tropical Agriculture, 1992)
The critical period of rice-weed competition was studied for the rice varieties Oryzica 1 and CICA 8, in 1989 and 1990. Weed species were: Eleusine indica, Echinochloa crus-galli, Echinochloa colonum, Cyperus difformis, Cyperus esculentus, Cyperus iria, Leptochloa filiformis, and Eclipta alba. Competition effects were similar for both varieties. Weeds emerging with the crop were the most damaging ones. Rice yields increased with longer weed-free periods up to 70 days after emergence (d.a.e.). No further yield increases resulted from longer weed-free durations. Weed emergence and growth after 70 d.a.e. was suppressed by the crop. Both rice cultivars required a critical height of 44 to 50 cm. to suppress weed growth 70 d.a.e. Though both varieties were equally weed suppressive by 70 d.a.e., leaf area index of CICA 8 was much larger than, that of Oryzica 1 when rice grew weed-free after emergence. Economic analysis showed that under heavy weed infestations, in a system where rice cannot be early and continuously flooded, three postemergent herbicide applications at 9, 18 and 44 d.a.e were justified.